Pastoral renewal in Włocławek Diocese in the light of resolutions of Synod conventions of Bishop Stanisław Karnkowski from year 1568 and 1579 - GRĘŹLIKOWSKI, JANUSZ (Prawo Kanoniczne, 2017)
Great and necessary gift of reform and pastoral renewal drawn up by Council of Trent was ardently and fruitfully taken up by Bishop Stanisław Karnkowski, and it was applied with great impact on two diocesan synods, which were held in 1568 and 1579. Synods’ resolutions strongly embedded in council decrees and provincial statutes regulated many sectors of pastoral life of contemporary kujawsko-pomorska diocese, activating clergymen as well as engaging the secular faithful people religion-wise and moral-wise. is outstanding legislator, reformer, grown and formed in Tridentinum atmosphere, supporter of Trent’s renewal of the Church and its priesthood structures, realized that renewal of priesthood and repair of religious-moral life has to nd its beginning in the reform of clergy, keeping the church discipline as well as in the life and conduct of the clerical conformable with the spirits of vocation for the ministry. Also the eorts aiming at better organization of deaneries served for renewal of priesthood as well as revival of deaneries’ activity, amongst the other, within the range of priesthood control, reminding the rectors their duties within the range of getting to know their parishioners, taking care of the sick and poor people, dispositions referring to defending the catholic faith threatened by reformation, regulations referring to teaching the Truths of the Faith, catechistic teaching, performing and taking the sacraments, Gods’ cult and liturgical issues. All of those was to serve post-council re- newal of priesthood in Włocławek’s Church. Bishop Stanisław Karnkowski realized his programmed actions curing and reforming the priesthood in dioceses not only by synodal activity, but also he supported them by Exhortations and Admonitiones issued by him – liturgical agenda, which served unication of liturgy and were the help for clergymen, not only in kujawsko-pomorska diocese. Analysis of his legisla- tive and ministry activity allows us to state, that he built in the diocese new structures of religious, priesthood and church life on the base of program laid out by Coucil of Trent. Hence he belonged to the most eminent Polish bishops of catholic Church, defender of the faith, promoter of education, reformer of habits and manner of the priest and secular faithful, and rst of all as outstanding and experienced jurisprudent of synodal legislation in Poland and reformer of the priesthood.